(untitled) (Scottish Historical and Archaeological Internet Reports, 2006)
The archaeobotanical evidence was restricted to charred plant remains as ground conditions on the site were not suitable for preservation of organic remains by waterlogging. The majority of samples contained low concentrations of carbonised cereal grains, weed seeds and charcoal. In addition, a number of samples contained the carbonised remains of legume seeds.